School Resilience and Social Support as Predictors of Academic Resilience among Full-Day Islamic School Students - depi_wulansari; Sunawan Sunawan (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
This study examines the influence of school resilience and social support on students’ academic resilience in Islamic full-day junior high schools. Academic resilience is increasingly important in intensive learning environments where students face prolonged academic and spiritual demands. It was hypothesized that school resilience and social support would significantly predict academic resilience, both partially and simultaneously. A quantitative correlational survey was conducted with 269 students selected through proportionate stratified random sampling. Data were analyzed using hierarchical regression. The results showed that school resilience significantly predicted academic resilience, particularly through teacher support and school safety. Social support also contributed significantly, although only family support showed a direct effect. Simultaneously, both predictors explained a meaningful proportion of variance in academic resilience. These findings highlight the importance of strengthening supportive school systems and family involvement to enhance students’ academic resilience.